The Effect Of Capital Expenditure On Environmental Performance With Investment As A Moderating Variable - Kusiyah; Eva Purnamasari; Asterina Anggraini; Parlindungan Dongoran; Yusran Zainuddin (Jurnal Teknologi dan Manajemen Industri Terapan, 2024)
This study aims to examine the effect of corporate Capital Expenditure (CAPEX) on Environmental Performance , and to analyze the role of Investment ( measured as a proportion of assets or strategic expansion) as a moderating variable in this relationship. Environmental performance is a crucial non-financial indicator in the context of corporate sustainability. Theoretically, allocating CAPEX to new assets (e.g., cleaner production technologies) is expected to improve environmental performance. However, the effectiveness of this capital expenditure is thought to depend heavily on the magnitude and strategic direction of the company's total investment. This research method uses a quantitative approach with secondary data from financial reports and sustainability reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2023. The Capital Expenditure variable is measured from the cash flow statement, Environmental Performance is measured using the PROPER score (Company Performance Rating Program in Environmental Management), and Investment is measured from total assets or sales growth rate. Data analysis was performed using Panel Data Regression through EViews 12 software, and Moderated Regression Analysis (MRA) to test the interaction hypothesis. The results of the study indicate that Capital Expenditure has a positive and significant influence on Environmental Performance. Furthermore, a key finding is that Investment is proven to significantly and positively moderate the relationship between Capital Expenditure and Environmental Performance (positive interaction variable coefficient, p < .05. This means that companies with high levels of investment tend to gain greater environmental performance benefits from each unit of environmental capital expenditure. The implications of this research highlight that CAPEX allocation for environmental purposes should be aligned with an integrated long-term investment strategy to maximize sustainability outcomes.